2018
DOI: 10.1177/1461444818755634
|View full text |Cite
|
Sign up to set email alerts
|

The social media see-saw: Positive and negative influences on adolescents’ affective well-being

Abstract: Social media use is nearly universal among US-based teens. How do daily interactions with social apps influence adolescents’ affective well-being? Survey self-reports (n = 568) portray social media use as predominantly positive. Exploratory principal component analysis further indicates that positive and negative emotions form orthogonal response components. In-depth interviews with a sub-sample of youth (n = 26), selected for maximum variation, reveal that affect experiences can be organized across four funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
200
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(230 citation statements)
references
References 39 publications
(60 reference statements)
24
200
0
6
Order By: Relevance
“…The present qualitative study explored adolescents' personal views and attitudes towards uses and key motivational factors for social media use and identified control processes related to motivations for SNS use in adolescence. Adolescents reported that SNS use formed a dominant part of their lives, offering both positive and negative affect experiences from use, and confirming previous findings (Weinstein, 2018). SNS use is part of a new youth culture with shared beliefs, rules, and meaning that is distinct from adult interaction (Vaterlaus et al, 2016).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The present qualitative study explored adolescents' personal views and attitudes towards uses and key motivational factors for social media use and identified control processes related to motivations for SNS use in adolescence. Adolescents reported that SNS use formed a dominant part of their lives, offering both positive and negative affect experiences from use, and confirming previous findings (Weinstein, 2018). SNS use is part of a new youth culture with shared beliefs, rules, and meaning that is distinct from adult interaction (Vaterlaus et al, 2016).…”
Section: Discussionsupporting
confidence: 84%
“…A growing body of literature provides evidence of stress, anxiety, compulsive and depressive symptomatology associated with excessive social media use (Barry, Sidoti, Briggs, Reiter, & Lindsey, 2017;Griffiths, Kuss, & Demetrovics, 2014;Griffiths et al, 2018;O'Keeffe, Clarke-Pearson, & Council on Communications and Media, 2011;Reid & Weigle, 2014;Royal Society for Public Health, 2017;Weinstein, 2018). Young people present with a paradox.…”
Section: Introductionmentioning
confidence: 99%
“…Community youth workers could incorporate these findings into curriculum and programming that empower and support youth to identify sources of healthy relationships, both with peers and with natural mentors. Additionally, the prevalence of new media (e.g., Instagram, Snapchat) in the lives of adolescents (Anderson & Jiang, ; Weinstein, ) provides numerous possibilities for community youth workers to tailor and disseminate information about health‐promotive behaviors to youth. In addition, within faith‐based contexts, African Americans report involvement with religious communities that ascribes to theologies and traditions which encourage congregants to explore and use their spiritual gifts and natural talents in relational contexts (see Mattis & Jagers, ; Woods‐Jaeger et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The studies on effects of SM have contradicting findings. Some examples where certain situations produce polar outcomes include studies on well-being, self-esteem, social adjustment, and social support for deployed service members [48,[52][53][54]. While only a few articles [e.g., 5, 6, 10, 17] found that Facebook use could lower depression, can lower anxiety, and can increase life satisfaction in certain situations -findings which contradict the majority of research -these contradictory studies are still worth expanding and reanalyzing, as causation and directionality are hard to establish regarding SM use and respective outcomes.…”
Section: Discussionmentioning
confidence: 99%